Monitoring and Evaluation for Results : Lessons from Uganda - Hauge, Arild O. (World Bank, Washington, DC, 2012)
Recent experience with monitoring and evaluation (M&E) in Uganda has shown how M&E can be developed to contribute to national capacity building, rather than become a demanding, but unproductive data collection exercise. Symptoms of M&E overload have been addressed by assigning coordination responsibility to the Office of the Prime Minister. Prospects are now improving for aligning M&E capacity with strengthening cost-effectiveness and achievement of value for money in service delivery.